Teaching Religious Character Education in Pre-School in the Era of Pandemic - Mar'atussholihah Kuswandi; Arif Rohman; Disa Hediansah (Nadwa: Jurnal Pendidikan Islam, 2021)
This study describes the learning process of religious-based character education at TK ABA Berbah, Sleman, during the Covid-19 pandemic. This study incorporates a qualitative research method with a descriptive case study approach. Findings suggest that the school implemented blended learning activities in which lessons are conducted online and offline. Habituation became a key activity during the offline session. The involvement of parents contributed to the success of learning during the pandemic, set an example, and monitor their kids at home. Blended learning provided an increase in the communication's intensity and the relationship between parents, children, and teachers so that teaching and learning religious-based character education can be conducted appropriately amid the Covid-19 pandemic.